Electability of Online Learning in The Perspective of Parents at MI Plus Al-Mahmud During The Covid-19 Pandemic - Wiwin Hunaida; Mihmidati Izmiyah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2020)
This research was conducted to know parents’ responses to online learning during the Covid-19 pandemic, which was implemented at MI Plus Al Mahmud Bacem following the decision of the minister of education and culture. This research uses descriptive quantitative research. Data collection using a questionnaire instrument, with a sample size of 91 parents of first-class and second class. Based on the questionnaire, 95.6 % of online learning made parents have more time with their children. 85.7 % of online learning made parents more compact with children. 100 % of online learning makes parents get to know their children's attitudes and character better. 45.1 % of online learning does not bother parents, and 49.5% of online learning does not make parents spend more to buy internet quota. While 49.5 % of online learning does not require parent's time, then 49.5 % of online learning does not make people's activities parents are disturbed. Furthermore, 47.3% of online learning does not make it difficult for children to understand learning material, and 40% of online learning does not make children bored quickly. As for 29.7%, online learning makes children more enthusiastic about learning, whilst 22.2% online learning makes children's interest even higher, and 41.1% of online learning with video media makes it easier to understand the lessons children. Then another, 76.9 % of learning online makes the child's learning hour has become flexible. 69.2% of online learning make children are spending more time in playing gadget with friends, 79.1% of online learning makes parents more creative in assisting children to learn.